2008
DOI: 10.1177/1938965508328716
|View full text |Cite
|
Sign up to set email alerts
|

Revenue Management's Renaissance

Abstract: The era has ended when revenue management can stand alone as a tactical approach to room management. With technological and management support, revenue management must be and is being integrated into all aspects of hotel management marketing and operating strategies. Going beyond its role of managing room inventory, revenue management will consider total revenue contributions, including group business and its ancillary revenues. Because prices are essentially transparent, hotels will need to consider customer … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
0
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 162 publications
(58 citation statements)
references
References 29 publications
2
44
0
3
Order By: Relevance
“…Another of the conclusions that this research reached was to validate the trend of rm as customer centric, mentioned by previous research (Cross, Higbie & Cross, 2009;noone, mCguire & roHFs, 2011) This research concludes and confirmed previous research that mentioned the strategy role of rm in the hotels (rannou anD melli, D., 2003;Cross, Higbie & Cross, 2009;kimes, s., 2010).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Another of the conclusions that this research reached was to validate the trend of rm as customer centric, mentioned by previous research (Cross, Higbie & Cross, 2009;noone, mCguire & roHFs, 2011) This research concludes and confirmed previous research that mentioned the strategy role of rm in the hotels (rannou anD melli, D., 2003;Cross, Higbie & Cross, 2009;kimes, s., 2010).…”
Section: Discussionsupporting
confidence: 75%
“…This research corroborates and validates the new skills required for Revenue Manager that earlier author mentioned (maC viCar anD roDger, 1996;kimes, s., 2008piCColi, 2008;brotHertHon anD mooney, 1992;Cross, Higbie & Cross, 2009;emeksiz, gursoy & iCoz 2006;griFFin, 1997). Where these skills were more focused on analytical skills than in operational skills such as rooms background .…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Previous research on literature stated that firms increase revenue through strategic orientation and the rate of innovation in the food service industry (Cross et al 2009;Dolores López-Gamero et al 2011;Rahman 2010). However, few studies have systematically investigated the relationship between integrated customer view and operational performance for food service companies.…”
Section: Introductionmentioning
confidence: 98%
“…The concern around Big Data is that managers might rely too much on the increased automation of data collection and turn their backs on intuition and instinct. Although price and revenue management decisions made in hotels are increasingly automated, particularly within major global brands such as Intercontinental Hotel Group (Koushik et al, 2012), the need for managers to understand the driving economic forces influencing the market and pricing are still necessary as a sense-check for the decisions made by automated revenue management systems, as part of the blend of art and science of revenue management (Cross et al, 2009). Some academics would argue that relying on Big Data in decisionmaking actually removes ambiguity and leads to more accurate decision-making (Davenport & Harris, 2007;Liberatore & Luo, 2010), but possibly in hospitality where human interactions are so central to the process, experience, intuition and instinct can still play a vital part in helping managers and employees make sense of and interpret data.…”
Section: Exploring Big Data's Impact On the Need For Economic Understmentioning
confidence: 99%